Sustainable Strategic Leadership and Organizational Goal - Ahmed, Tahmid (My University, 2025)
This thesis examines Sustainable Strategic Leadership (SSL) as one of the key elements of attaining long-term organizational objectives and competitive advantage. Combining the environmental, social and economic facets with the theory of leadership, the research relies on the practice theory, organizational cognition and institutional work approaches to describe the process of making the notion of sustainability a part of the routine of the organization. The qualitative multi-case study method was utilized in data collection where interviews and document analysis were combined in data analysis using the thematic and configurational approaches. The results indicate that the behaviour of leaders including stakeholder engagement, performance system redesign and symbolic behaviour establishes cognitive, institutional and cultural processes between sustainability and performance. The research has not only its theoretical but also practical implications as well since it provides an example of how leadership can turn sustainability not only into rhetoric but also routinized strategic reality.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development